Nurses’ Perceptions of Spirituality and Spiritual Care at Five Tertiary Care Hospitals in Riyadh, Saudi Arabia: A Cross-Sectional Study - Kaddourah, Bayan (Oman Med J, 2018)
OBJECTIVES: To identify the perceptions towards spirituality and spiritual care among nurses at tertiary care hospitals in Riyadh, Saudi Arabia. METHODS: A cross-sectional study was conducted on nurses at five tertiary care hospitals in Riyadh. The data were collected using the Spirituality and Spiritual Care Rating Scale (SSCRS). RESULTS: We recruited 978 nurses, of which 896 (91.6%) were female. The mean SSCRS score was 3.8±0.5 (the spirituality and spiritual care statements fell within the ‘agree’ category). A statistically significant difference was found only between perceptions of spirituality and spiritual care among nurses and their nursing experience duration. CONCLUSIONS: The findings of this study revealed that nurses were oriented to spirituality, and respected the importance of providing spiritual care to their patients. The nurses believed that spirituality exists in all religions and spiritual care means showing concern while treating the patients by focusing on respecting patients’ religious beliefs.